Digital diplomacy activities of Hungarian governmental actors on Twitter (2021-2022) - Kacziba, Péter (POLARITIES, 2023)
The study focuses on the empirical study of Twitter users associated with the Hungarian government between 2021 and 2022. The aim of the study is to map the composition of those government actors who have been most active on the platform, to understand their posting practices, and to identify the main indicators of the published narratives and the trends of their distribution. To achieve these objectives, the research conducted an independent data collection and used software analysis to examine the generated database. The analysis has outlined a digital diplomacy activity in line with international trends, with a relatively high number of government users and a proactive involvement of certain emblematic figures. The results indicate the characteristics of a centralized structure that became less controlled with distance from the core. In terms of content categories, the research revealed a mostly balanced distribution of informational and relational components. However, these characteristics were only valid when considering the overall average and were mainly caused by the influence of the year 2021. In the second year of the sample, shifts can be observed as messages typically framed for the international context increasingly began to incorporate communication panels used for domestic audiences.